2010
DOI: 10.1136/adc.2009.180216
|View full text |Cite
|
Sign up to set email alerts
|

Variation in recording of child maltreatment in administrative records of hospital admissions for injury in England, 1997-2009

Abstract: Despite a shift from maltreatment syndrome to codes for maltreatment-related features, the overall burden has remained stable. In combination, the cluster of codes related to maltreatment identify children likely to meet thresholds for suspecting or considering maltreatment and taking further action, as recommended in recent National Institute of Health and Clinical Excellence guidance, and indicate a considerable burden to which hospitals should respond.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 27 publications
(27 reference statements)
5
55
0
2
Order By: Relevance
“…매년 100만 명 이상의 18세 이하 소아청소년환자들이 응급실을 방문하고 있으며 이는 우리나라 소아청소년의 약 10%에 해당되는 인구이다 7,8) . 응급실 방문 소아 중의 아동학대 비율에 대해서는 국가마다 큰 차이를 보고 있는 데, 영국의 경우 1.4~6.5%, 이탈리아의 경우 2%, 네덜란 드의 경우 0.2%, 미국의 경우 10%까지 보고하고 있다 [9][10][11][12][13][14] . 16) and Pearce 12) et al 33) Findings examination conform history …”
Section: Review Articleunclassified
“…매년 100만 명 이상의 18세 이하 소아청소년환자들이 응급실을 방문하고 있으며 이는 우리나라 소아청소년의 약 10%에 해당되는 인구이다 7,8) . 응급실 방문 소아 중의 아동학대 비율에 대해서는 국가마다 큰 차이를 보고 있는 데, 영국의 경우 1.4~6.5%, 이탈리아의 경우 2%, 네덜란 드의 경우 0.2%, 미국의 경우 10%까지 보고하고 있다 [9][10][11][12][13][14] . 16) and Pearce 12) et al 33) Findings examination conform history …”
Section: Review Articleunclassified
“…With abuse, a risk for false positive diagnosis might arise because even expert practitioners may overestimate the probability of rare but significant events (Lichtenstein et al 1978), particularly if the suspected event would trigger an action by the practitioner that would protect a child from possible harm (Tversky and Kahneman 1981). Conversely, fear of professional censure for an erroneous diagnosis, if sufficiently intense, could lead to a framing effect towards underdetection, as found by González-Izquierdo et al (2010). The simple collection of additional confirmatory data also has risks, as excessive information has been associated with impaired practitioner comprehension (White et al 2010) and catastrophic false negative judgments about children being at risk of significant harm (Munro 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In the courts, the paediatrician functions as an expert witness i.e., a witness whose opinions are taken as evidence by the court, additional to any factual evidence it accepts. In the United Kingdom, public confidence in medico-legal caused UK paediatricians to become less willing to work with potential child abuse cases (Mathews et al 2009) or make diagnoses of abuse (González-Izquierdo et al 2010). US paediatricians' perceptions of child abuse processes also moderated their willingness to report or investigate abuse (Flaherty, Sege, and Hurley 2008), resulting in inconsistent reporting and systemic bias Lindberg et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…1 Previous research using similar definitions of maltreatment to those used in the current study found that there was a coded maltreatment-related concern in 3% (95% CI = 2.7 to 3.1) of all acute injury admissions for children aged . 20 Future linkage of GP data to routine hospital data or social care data is needed to explore which children are being recognised by different professionals.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…Concerns about maltreatment are recorded in routine health records using a wide variety of codes, including those that are indirect or euphemistic. 19,20 To reflect this, a list of Read Codes were developed that were maltreatment-related, ranging from codes likely to be specific (for example, child protection plan or physical abuse of child), to codes anticipated to be more sensitive, indicating high child welfare need or concerns about parenting (Box 2). For analysis, codes were grouped into four categories.…”
Section: Phase 1: How Do Gps Record Known Cases Of Child Maltreatment?mentioning
confidence: 99%